Tabligh Jamaat Preaching Strategy In Improving Religious Understanding - Fatanah, Nurul; Nurkidam, Andi; Haramain, Muhammad (Institut Agama Islam Negeri Parepare, 2022)
The type of research used in this study is descriptive qualitative method, the data in this study were obtained from primary data and secondary data. Data collection techniques used are observation, interviews, and documentation. The data analysis technique is using qualitative data analysis. The results of this study indicate that the da'wah strategy carried out by tablighi congregations in increasing religious understanding in the community in Batubatu Kec. Duampanua Pinrang Regency using good da'wah strategies, namely: 1) Recitation Strategy, 2) Tazkiyah Strategy, and 3) Ta'lim Strategy with several regular congregational activities in carrying out da'wah such as Jaulah, Khuruj, Ta'lim wa Ta'lum, Gathering, Mudzakarah, and Deliberation. The influence of the Tabligh Congregation in Batu Batu is quite good, as can be seen from the presence of some people who emigrated to join the congregation's activities and became more obedient to religious teachings